Arabica‑cofee and teobroma‑cocoa agro‑industrial waste biosorbents, for Pb(II) removal in aqueous solutions - Ángeles Suazo, Julio Miguel (2022)
Agro-industrial waste biosorbents of arabica–cofee (WCA) and theobroma–cocoa (WCT) have been characterized and tested to remove Pb(II) from aqueous media. The maximum adsorption capacity of WCA and WCT (qmax = 158.7 and 123.5 mg·g−1, respectively) is comparable or even higher than for several other similar agro-industrial waste biosorbents reported in the literature. Structural and morphological characterization were performed by infrared spectrometry with Fourier transform (FT-IR), scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM/EDS), and charge measurements at the zero point charge (pHPZC). Both biosorbents, WCA and WCT, show cracked surfaces with heterogeneous plates which ones include functional adsorption groups such as OH, C = O and C-O-C. Optimal Pb(II) adsorption occurs for a pH between 4 and 5 at [WCA] and [WCT] dose concentrations of 2 g·L−1. We found that the adsorption process follows pseudo-second order kinetics with a rapid growth rate (almost six times larger for WCA than for WCT), basically controlled by the chemisorption process. The regeneration of both biosorbents was carried out in an eluent of 0.1M HNO3 and they can be eficiently reused up to 5 times.